A mother's deficiency, a baby's challenge: vitamin B12 deficiency-related seizures and pancytopenia in an infant - Rebelo, Ana; Serôdio, Margarida; Caetano, Francisco Branco; Pereira, Andreia Gomes; Maia, Raquel (International Journal Of Community Medicine And Public Health, 2024)
Anemia is prevalent in pediatric age and it stems from diverse factors. While iron deficiency is a common cause above six months of age, other nutritional deficits contribute to the disease burden. During pregnancy, anemia due to nutritional deficits is associated with adverse outcomes for the newborn. Precise diagnosis of dietary deficits in the pediatric population is vital to avert negative health consequences. We describe the case of a six-month-old exclusively breastfed infant with a mother having unspecified anemia under folic acid supplementation. The infant presented with neurological symptoms, including paroxysmal events and developmental regression. Laboratory analysis revealed pancytopenia and severe vitamin B12 deficiency. The patient’s mother's serum level of vitamin B12 was also low and ant parietal cell antibodies were positive, suggesting maternal autoimmune gastritis. Treatment with hydroxocobalamin led to clinical and analytical improvement. Maternal deficiency is the major cause of cobalamin deficiency in infants. It is paramount to raise awareness to this issue to prevent its avoidable repercussions.